Strengthening Islamic Religious Education Research Based on Socio-Cultural Change among Teachers at State Eelementary School of Toviora, Lalundu District, Donggala Regency - Rustina, Rustina; Suharnis, Suharnis; Restu Pauzia; Nasrul, Nasrul (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2025)
This study examines efforts to strengthen Islamic religious education research based on social and cultural change among teachers at SDN Toviora, Donggala Regency, as well as the impact of such efforts on teachers. Data were collected through in depth interviews and analyzed using a descriptive qualitative approach. The research participants were selected purposively based on predetermined criteria, consisting of the school principal and several teachers considered credible sources of information at SDN Toviora. The findings show that strengthening efforts are mainly carried out through training programs and research workshops for teachers. These activities positively affect teachers motivation to conduct research and contribute to social and cultural change within teachers. The findings also highlight the emergence of a new principle in which becoming a teacher researcher is viewed as a way to develop teacher competence and to affirm the role of teachers as agents of change. This study implies that improving the quality and quantity of professional teachers requires greater seriousness in learning and increased innovation, so that teachers are better prepared to face ongoing changes in society..